STRATEGI KOMUNIKASI PEMASARAN DESA WISATA KAYANGAN DI DESA BRUBUH NGAWI MELALUI MEDIA MASSA DAN MEDIA SOSIAL (Universitas Negeri Surabaya, 2022)
The tourism sector in alternative tourism is currently a trend that is favored by the community, tourism that carries the concept of being more friendly to nature and local communities and is able to make and facilitate villages to develop into tourist attractions. Kayangan Tourism Village in Brubuh Ngawi Village is a new tourist village whose initial operation has been affected by the pandemic. Therefore, Kayangan Tourism Village must be able to compete with other tourism with various strategies in marketing and maintaining it. This study aims to describe the marketing communication strategy used by Kayangan Tourism Village. The method used is descriptive qualitative. Data obtained from the results of observations and interviews. The results of this study show that Kayangan Tourism Village uses marketing strategies in the form of collaborating with mass media and online medai, collaborating with artists and content creators, focusing on social media and electronic- word of mouth. Keywords : Marketing communication strategy, Mass Media, Social Media, Kayangan Tourism Village